Development of a novel NURR1/NOT agonist from hit to lead and candidate for the potential treatment of Parkinson's disease. Issue 7 (1st April 2019) - Lesuisse, Dominique; Malanda, André; Peyronel, Jean-François; Evanno, Yannick; Lardenois, Patrick; De-Peretti, Danielle; Abécassis, Pierre-Yves; Barnéoud, Pascal; Brunel, Pascale; Burgevin, Marie-Claude; Cegarra, Céline; Auger, Florian; et al.
Graphical abstract: Abstract: In the course of a programme aimed at identifying Nurr1/NOT agonists for potential treatment of Parkinson's disease, a few hits from high throughput screening were identified and characterized. A combined optimization pointed to a very narrow and stringent structure activity relationship. A comprehensive program of optimization led to a potent and safe candidate drug displaying neuroprotective and anti-inflammatory activity in several in vitro and in vivo models.